The Effect Of Marketing Communication Strategy Big Sale Shopee On Purchasing Decision Of Students Of The University Of Ratu Samban - Tika , Yori Manis; Astuti , Linda; Susanto , Prio (GAYAKU PUBLISHER, 2023)
Purpuse transaction in the market place grow rapidly from year to year, with high penetration of internet user, especially at the age of 19-24 years. The purpose of this research is to find out big sale on the purchashing decisions of ratu samban university students. The type of research used is qualitative. The Data collection technisques were performed by disseminating questionnaires to 96 students. The sampling technique used is simple random sampling. Hypothetical testing data is conducted with a simple linear regression test through the SPSS 26 program. The result showed that partially the variable Big Sale had a significsnt effect on the purchasing decision of ratu samban university students.